Can agricultural insurance enhance comprehensive grain production capacity? Mechanisms of risk protection and production incentives - Hou, Dainan; Wang, Xin (Frontiers in Sustainable Food Systems, 2025)
IntroductionFood security is essential for national development, and agricultural insurance is a crucial tool for managing agricultural risks. It plays a key role in enhancing grain production capacity, but its impact across various dimensions has not been thoroughly examined.MethodsThis study develops a multidimensional model of comprehensive grain production capacity based on production function theory. The model incorporates labor productivity, land use efficiency, agricultural technological innovation, and agricultural carbon emissions. We use panel data from 27 Chinese provinces spanning from 2009 to 2021 and apply a fixed-effects model to assess the effects of agricultural insurance on these dimensions. Robustness and endogeneity tests are conducted to ensure the validity of the results.ResultsOur findings demonstrate that agricultural insurance significantly improves overall grain production capacity. The positive effects are particularly notable in labor productivity, land use efficiency, technological innovation, and a reduction in agricultural carbon emissions. Moreover, the impacts are more pronounced in non-major grain-producing areas compared to major ones.DiscussionThese results suggest that agricultural insurance has a vital role in enhancing sustainable grain production. We recommend that policymakers and insurers focus on strengthening the role of agricultural insurance, especially in regions that are less involved in major grain production.